Do agents care for the mission of their job? A field experiment - Vanessa Mertins; Sabrina Jeworrek (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Economic theory suggests that agents care for the outcomes they produce. This paper studies the conditions under which a pro-social mission of a job affects workers motivation to perform well. In particular, we investigate whether it makes a difference if workers actively decide upon doing a mission-oriented job or are exogenously assigned. We find that a pro-social mission itself affects only a small group of workers in a positive way whereas self-selection into a mission-oriented job leads to a highly significant overall performance boost.
Keywords: C93; J33; M55; 330